Response of Nitrifier and Denitrifier Abundance and Microbial Community Structure to Experimental Warming in an Agricultural Ecosystem - Waghmode, Tatoba R.; Chen, Shuaimin; Li, Jiazhen; Sun, Ruibo; Liu, Binbin; Hu, Chunsheng (Frontiers in Microbiology, 2018)
Soil microbial community plays an important role in terrestrial carbon and nitrogen cycling. However, the response of the soil nitrifier and denitrifier communities to climate warming is poorly understood. A long term field warming experiment has been conducted for 8 yrs at Luancheng Experimental Farm Station on the North China Plain, we used this field to examine how soil microbial community structure, nitrifier and denitrifier abundance respond to warming under regular (RI) and high irrigation (HI) at different soil depths (0-5 cm, 5-10 cm and 10-20 cm). Nitrifier, denitrifier and the total bacterial abundance were assessed by quantitative PCR of the functional genes and 16S rRNA gene, respectively. Bacterial community structure was studied through high throughput sequencing of the 16S rRNA gene. Under RI, warming significantly (P<0.05) increased the potential nitrification rate and nitrate concentration and decreased the soil moisture. In most of the samples, warming increased the AOB (ammonia-oxidizing bacteria) abundance but decreased the AOA (ammonia-oxidizing archaea) and denitrifier (nirK, nirS and nosZ gene) abundance. Under HI, there was a highly increased AOA and 16S rRNA gene abundance and a slightly higher denitrifier abundance compared with RI. Warming decreased the bacterial diversity and species richness, and the microbial community structure differed greatly between the warmed and control plots. The decrease in bacterial diversity was higher in RI than HI and at the 0- to 5-cm depths than at the 5- to 10-cm and 10- to 20-cm soil depths. Warming led to an increase in the relative abundance of Actinobacteria, Bacteroidetes and TM7 but a decrease in Acidobacteria, Alphaproteobacteria, Deltaproteobacteria, Nitrospira, and Planctomycetes. The greater shift in microbial community structure was only observed in RI at the 0- to 5-cm soil depth. This study provides new insight into our understanding of the nitrifier and denitrifier activity and microbial community response to climate warming in agricultural ecosystems.